Predictors of Emotional Intelligence Among Undergraduate Students - Wong, Sook Khuan (2017)
Emotional intelligence was one of the paradigms most researched on. It was a wide area and yet the most prevalent frameworks of emotional intelligence would be Mayer and Salovey and Goleman. Mayer and Salovey (1995) defined emotional intelligence as the ability to perceive accurately, appraise, and express emotion; the ability to access and/or generate emotion and emotional feelings when they facilitate thought; the ability to understand knowledge; and the ability to regulate emotions to promote emotional and intellectual growth. Whilst Goleman (1995) defined emotional intelligence as comprised of five elements which included self-awareness, ability to manage moods (self-regulation), self- motivation, social awareness (empathy) and social skills such as cooperation and leadership. This research was set against the background of Malaysian higher education whereby emotional intelligence among students was considered at its infancy stage. It was imperative to understand the role of emotional intelligence in higher education system in Malaysia. In particular, there was a need to find out whether students who perform better academically and who were able to learn with different learning styles were highly emotionally intelligent individuals. As such, this research would utilize Goleman’s model of emotional intelligence for the theoretical framework as a basis for any new findings that could contribute to knowledge and theory. The purpose of the research was to test the relationship and influences of emotional intelligence on students’ academic performance, non-cognitive factors such as life satisfaction and stress tolerance, leadership qualities and students’ learning styles among the undergraduate students in higher learning institutions. Furthermore, this research aimed to examine the differences between demographic factors and emotional intelligence. Data were collected from questionnaires prepared to the undergraduate students of two colleges whereby the samples of 300 respondents were selected. The model and data were then tested by using Multiple Regression Analysis. Results from the research showed that there were relationship between emotional intelligence and students’ academic performance, non-cognitive factors of life satisfaction and stress tolerance, leadership qualities and students’ learning styles. Further to that, it was found that there existed significant differences between emotional intelligence and some of the demographic factors. In summary, this research found that there was a significant element that could be developed to the model which contributed to knowledge and existing theories of emotional intelligence